2002
DOI: 10.1016/s0014-5793(02)03181-2
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas, a model system for studying the assembly and dynamics of photosynthetic complexes

Abstract: The green unicellular alga Chlamydomonas reinhardtii has emerged as a powerful model system for studying the biosynthesis of the photosynthetic apparatus and the acclimation of this system to changes in light conditions. The assembly of the photosynthetic complexes involves the coordinate interaction between the nuclear and chloroplast genetic systems. Many factors involved in speci¢c chloroplast post-transcriptional steps have been identi¢ed and characterized. Chlamydomonas is able to adapt to changes in ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 35 publications
1
72
0
1
Order By: Relevance
“…However, at light intensities of Ͼ400 mol⅐m Ϫ2 ⅐s Ϫ1 , the NPQ of the mutant was significantly higher than that of the wild type. Further analysis revealed that the additional NPQ was not rapidly reversible, The plants shown in C were exposed to illumination (300 mol⅐m Ϫ2 ⅐s Ϫ1 ) for 2 days after 7 weeks of growth in low light (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) mol⅐m Ϫ2 ⅐s Ϫ1 ). indicating that the increased NPQ is due to a larger component of photoinhibitory quenching in the mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at light intensities of Ͼ400 mol⅐m Ϫ2 ⅐s Ϫ1 , the NPQ of the mutant was significantly higher than that of the wild type. Further analysis revealed that the additional NPQ was not rapidly reversible, The plants shown in C were exposed to illumination (300 mol⅐m Ϫ2 ⅐s Ϫ1 ) for 2 days after 7 weeks of growth in low light (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) mol⅐m Ϫ2 ⅐s Ϫ1 ). indicating that the increased NPQ is due to a larger component of photoinhibitory quenching in the mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work has shown that proteins functional in the translation and import of subunit proteins are required for the biogenesis of photosynthetic complexes (4,28). However, the proteins that function specifically in the assembly of the complexes have long been a mystery and are only now beginning to be identified (29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…The single-celled motile freshwater alga Chlamydomonas reinhardtii is a model system for studying photosynthesis, which is useful to complement and extend the understanding of photosynthetic eukaryotes when compared with Arabidopsis thaliana (Rochaix, 2002;Gutman and Niyogi, 2004). Chlamydomonas is a photoautotrophic organism in the wild and is exposed to a complex light environment that includes UV-B.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, microalgal oil and biomass production has shown promise (Chisti, 2007;Ohlrogge et al, 2009;Williams and Laurens, 2010;Atabani et al, 2012) because of the photoautotrophic growth of algae and their ability to reach high cell densities and accumulate high dry weight percentages of triacylglycerol (TAG) and their potential for much higher productivity per hectare than terrestrial biofuel crops (Hu et al, 2008;Wijffels and Barbosa, 2010). The unicellular green alga Chlamydomonas reinhardtii is among the most widely studied models of photosynthesis (Rochaix, 2002) and other cellular processes, including lipid accumulation by algae under stress . Its advantages for studying photosynthetic mechanisms and regulation include the ability to grow both photo-and heterotrophically so that photosynthetic down-regulation and photosynthetically impaired mutants can be isolated (Dent et al, 2001) and a fully sequenced genome, collections of mutants, and the ease with which its growth, physiology, and photosynthetic rates can be measured.…”
mentioning
confidence: 99%